Experimental Investigation of Pervaporation Membranes for Biobutanol Separation - Heitmann, S.; Krüger, V.; Welz, D.; Lutze, P. (Journal of Membrane and Separation Technology, 2013)
Biotechnological production of chemical building blocks is one important step towards a more sustainable production. Unfortunately, the products to be separated are often highly diluted. Pervaporation has received increasing attention for the separation of small amounts of organic compounds from aqueous solutions, especially in the separation of butanol from water or from fermentation broth. To evaluate the potential of pervaporation for biobutanol recovery a consistent database is required, describing the dependency of permeate fluxes and selectivities on process variables like temperature, permeate pressure as well as feed concentrations and compositions. Therefore, within this work we investigated the separation behaviour of a commercially available polydimethylsiloxane (PDMS) membrane and membranes based on poly(ether block amide) (PEBA) fabricated in our own laboratory. The membranes were tested under varying operating conditions. Fermentation by-products or impurities may affect the pervaporation separation performance. Therefore, in addition, the permeate fluxes and the influence of acetone, ethanol, acetic and butyric acid and 1,3-propanediol have been investigated in detail as well. Several differences in the permeability and selectivity of PDMS and PEBA were observed during the experimental study. Swelling experiments were applied to further analyse the separation behaviour of PDMS and PEBA more in detail. Finally the influence of the observed separation performances on the overall butanol pervaporation process is discussed. It was found that especially well permeating by-products like acetone can drastically influence the subsequent downstreaming process.